A Demographic Perspective on Gender, Family and Health in Europe - Jordi Gumà (Springer Nature, 2018)
This open access book examines the triangle between family, gender, and health in Europe from a demographic perspective. It helps to understand patterns and trends in each of the three components separately, as well as their interdependencies. It overcomes the widely observable specialization in demographic research, which usually involves researchers studying either family or fertility processes or focusing on health and mortality.